Gambaran Kualitas Hidup Berdasarkan Karakteristik Klinis dan Sosiodemografi Pasien Penyakit Ginjal Kronis Stadium Akhir di RSUD Welas Asih - Erwin Ferdiansyah Mursidi; Maria Komariah; Sri Hartati Pratiwi (Universitas Malahayati Lampung, 2026)
ABSTRACT Patients with end-stage chronic kidney disease (CKD) often experience physical and psychological effects, as well as limitations in activities of daily living and social interactions. This condition requires patients to undergo lifelong renal replacement therapy such as hemodialysis. Dependence on this long-term therapy affects physical and psychological conditions and functional status, which significantly impacts patients' quality of life. This study aims to identify the quality of life based on the clinical and sociodemographic characteristics of end-stage chronic kidney disease patients at RSUD Welas Asih. This study is a quantitative descriptive survey using secondary data from the study ‘Harmony in Health: The Intersection of Natural Resources and Well-Being’. The study population consisted of patients diagnosed with end-stage CKD undergoing routine therapy at the hemodialysis unit of RSUD Welas Asih. The sample consisted of 111 respondents selected using convenience sampling according to the inclusion criteria. The quality-of-life measurement instrument used the WHOQOL-BREF questionnaire, which has been tested for validity and reliability. Data analysis used univariate analysis. The results showed that, in general, the quality of life of patients was in the good category (60.4%). Based on the domains, the quality of life in the psychological, social, and environmental domains tended to be good, but most respondents had a poor quality of life in the physical domain (65,8%). Good quality of life was predominantly found in younger age groups, those with higher education levels, those without comorbidities, and those who had undergone hemodialysis for ≥1 year. The conclusion of this study is that although the quality of life of patients was generally good, the physical domainon was still the most affected aspect, requiring nursing interventions focused on the management of physical complaints. Keywords: Chronic Kidney Disease, Hemodialysis, Quality of Life, WHOQOL-BREF. ABSTRAK Pasien penyakit ginjal kronis stadium akhir sering kali merasakan dampak fisik, psikologis, serta keterbatasan dalam aktivitas sehari-hari (Activities of Daily Living) dan interaksi sosial. Kondisi ini mengharuskan pasien menjalani terapi pengganti ginjal seumur hidup seperti hemodialisis. Ketergantungan pada terapi jangka panjang ini memengaruhi kondisi fisik, psikologis, dan status fungsional yang berdampak signifikan terhadap kualitas hidup pasien. Penelitian ini bertujuan untuk mengidentifikasi gambaran kualitas hidup berdasarkan karakteristik klinis dan sosiodemografi pasien penyakit ginjal kronis stadium akhir di RSUD Welas Asih. Penelitian ini merupakan penelitian survei deskriptif kuantitatif menggunakan data sekunder dari penelitian “Harmony in Health: The Intersection of Natural Resources and Well-Being”. Populasi penelitian adalah pasien dengan diagnosa penyakit ginjal kronis stadium akhir yang menjalani terapi rutin di instalasi hemodialisis RSUD Welas Asih. Sampel berjumlah 111 responden yang diambil menggunakan teknik convenience sampling sesuai kriteria inklusi. Instrumen pengukuran kualitas hidup menggunakan kuesioner WHOQOL-BREF yang telah teruji validitas dan reliabilitasnya. Analisis data menggunakan analisis univariat. Hasil penelitian menunjukkan bahwa secara umum kualitas hidup pasien berada pada kategori baik (60,4%). Berdasarkan domain, kualitas hidup pada domain psikologis, sosial, dan lingkungan cenderung baik, namun sebagian besar responden memiliki kualitas hidup buruk pada domain kesehatan fisik (65,8%). Kualitas hidup yang baik dominan ditemukan pada kelompok usia muda, tingkat pendidikan tinggi, tidak memiliki penyakit penyerta, dan telah menjalani hemodialisis ≥1 tahun. Simpulan penelitian ini adalah meskipun secara umum kualitas hidup pasien baik, domain fisik masih menjadi aspek yang paling terdampak sehingga memerlukan intervensi keperawatan yang berfokus pada manajemen keluhan fisik. Kata Kunci: Penyakit Ginjal Kronis, Hemodialisis, Kualitas Hidup, WHOQOL-BREF.